Ultrasound Findings of Neck in Paediatric Patients with Hypothyroidism in Tertiary Care Hospital (Medical Forum Monthly, 2023)
Objective: To evaluate ultrasonographic features of hypothyroidism in children at tertiary care hospital.Study Design: Prospective cross sectional studyPlace and Duration of Study: This study was conducted at the Department of Paediatrics, Children Hospital, Pakistan Institute of Medical Sciences, Islamabad from 1st January 2022 to 30th June 2022.Materials and Methods: Fifty children who were less than 12 years with hypothyroidism were enrolled. The children with comorbid conditions and not willing to participate were excluded. The medical reports of children presenting with hypothyroidism and swelling in front of neck were evaluated after their consent by ultrasonography.Results: The mean age of patients was 5.91±2.24. There were 27 (54%) were males and 23 (46%) were females. Fourteen (28%) had hypogenous type of echotexture, 2 (4%) had normal type of echotexture and 34 (68%) had heterogeneous echotexture. Majority of the participants had cyst i.e. 31 (62%) and 33 (66%) had lymphadenopathy. There was insignificant association of lobe size with age (p>0.05).Conclusion: Ultrasound scanning is a non-invasive, widely accessible, and less expensive technique for diagnosis of thyroid disorder. In the investigation and treatment of thyroid problems, thyroid ultrasonography has become a well-known and effective tool.